Definitive Business Plan, Second Edition, The - Stutely, Richard (Pearson, 2002)
Accessible to both the entrepreneur and the experienced executive, this second edition of The Definitive Business Plan is the fast track to intelligent business planning. This international bestseller is THE ultimate guide to business planning. Whether your goal is to launch a new business or secure corporate support for a new venture, it will help you build a plan capable of driving and directing a robust business.